2022
DOI: 10.1038/s41612-022-00272-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and characteristics of dry and moist heatwaves over East Asia

Abstract: The increasing frequency of heatwaves over East Asia (EA) is impacting agriculture, water management, and people’s livelihood. However, the effect of humidity on high-temperature events has not yet been fully explored. Using observations and future climate change projections conducted with the latest generation of Earth System models, we examine the mechanisms of dry and moist heatwaves over EA. In the dry heatwave region, anticyclonic circulation has been amplified after the onset of heatwaves under the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…For example, Ha et al. (2022) revealed that the intensification of dry heat wave events over northern China and Mongolia was simulated under the future emission scenario of phase six of the Coupled Model Intercomparison Project (see also Figure 6 of Ha et al., 2022).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ha et al. (2022) revealed that the intensification of dry heat wave events over northern China and Mongolia was simulated under the future emission scenario of phase six of the Coupled Model Intercomparison Project (see also Figure 6 of Ha et al., 2022).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Especially, the suggestion that heat wave in the focusing area can continue and become intensified in the future supports the importance of the implications mentioned in this study. For example, Ha et al (2022) revealed that the intensification of dry heat wave events over northern China and Mongolia was simulated under the future emission scenario of phase six of the Coupled Model Intercomparison Project (see also Figure 6 of Ha et al, 2022).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, due to regional dependence of climate change, the changes in the number and composition of thermal stress types can vary greatly across space. Indeed, regional studies have reported an imminent "extinction" of thermal winters 23,24 , a significant reduction in the number of comfortable days 25 , a large increase in the frequency of hot weather [26][27][28][29] and more extreme heat events intensified by high humidity in low-latitude regions [30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…These hazards have increased through two or more extreme events co-occurring, an extreme event amplifying with climate conditions, or a combination of events leading to extreme event [2][3][4][5] . Thus, it is essential to understand the process and cause of unusual weather/climate phenomena to reduce the loss of socio-economic and human activities.…”
Section: Introductionmentioning
confidence: 99%